Land titles, credit markets and wealth distributions - James C. MacGee (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Does the existence of formal title to land and real estate matter for the distribution of wealth? This paper reviews the empirical literature on the economic impact of land and real estate administration systems across countries. This paper argues that a functioning credit market for secured credit is necessary to realize the full benefits of legal title to private real estate. This paper also reviews quantitative economic theory on wealth distribution to assess the likely impact of different land registration systems on wealth inequality. The implication of current theory is that poor land administration systems may sometimes lead to lower levels of wealth inequality than better land registration systems.
Keywords: E21; K11; 330; land titles; credit markets; wealth distribution; Bodenrecht; Kreditmarkt